Fresno County Young Lawyers Association Halloween Dance at Crossland's Barn - Watkins, Howard::::::::: (1984)
Fran Christiansen and Jim Christiansen in space outfits, Tomar Mason as Nefertiti, Barbara St. Louis as college coed and Bob Knight wearing black mask